2019
DOI: 10.1515/jcim-2018-0100
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis, cytotoxic and antioxidant activities of Myrtus communis essential oil from Morocco

Abstract: Background Myrtus communis L. is an aromatic evergreen plant common in Morocco. In addition to its culinary uses, it has been used medicinally as a disinfectant, an antiseptic or as a hypoglycemic agent. However, its cytotoxic activity has not been well investigated so far. The current study describes the chemical composition, cytotoxic and antioxidant activities of Myrtus communis L essential oil obtained from different regions of Morocco. Methods Myrtus communis essential oils were obtained by hydrodistill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…In fact, they are able to react with peroxyl radicals, as demonstrated by Origanum vulgaris essential oil, whose most relevant compounds are thymol and carvacrol [ 9 , 12 ], Thimus capitatus essential oil, whose most relevant compound is still carvacrol [ 25 ], and many others [ 35 , 36 ]. A comparable antioxidant activity was also exerted by the citral loaded liposomes due to citral, an aldehydic terpene [ 37 ], as previously reported [ 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 77%
“…In fact, they are able to react with peroxyl radicals, as demonstrated by Origanum vulgaris essential oil, whose most relevant compounds are thymol and carvacrol [ 9 , 12 ], Thimus capitatus essential oil, whose most relevant compound is still carvacrol [ 25 ], and many others [ 35 , 36 ]. A comparable antioxidant activity was also exerted by the citral loaded liposomes due to citral, an aldehydic terpene [ 37 ], as previously reported [ 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 77%
“…The apoptosis of MCF7 was stimulated by Ocimum sanctum EO with the regulation of apoptotic genes p53 and Bid and elevation of Bax/Bcl-2 [15]. Similar results were found with MCF7 apoptosis induction by Tetraclinis articulata [16] and Myrtus communis L., commonly used in Morocco for culinary purposes [17]. Carvacrol is the major ingredient of Zataria Multiflora EO and induced apoptosis in 2D and 3D cell cultures of MDA-MB-231, MCF7, and T47D with selectivity and increased reactive oxygen species (ROS) generation, loss of mitochondrial membrane potential (ΔΨm), caspase 3 activation, and DNA damage [18].…”
Section: Induction Of Apoptosis In Breast Cancer Cells By Essential Oilssupporting
confidence: 72%
“…(7.46%-35.72%) [27] and A. millefolium L. (1.2%-19.8%) [28]. Previous studies on 1,8 cineole, or on EOs containing it, reported apoptotic effects on a variety of cancer cell lines, including: SK-MEL-28 (human melanoma); A549 (human lung carcinoma); Colo-205 (Human Caucasian colon adenocarcinoma); (SiHa) cells (human cervical carcinoma); Hep-G2 (hepatocellular carcinoma); MCF-7, T47D, MDA-MB-231 (human breast adenocarcinoma); RKO (Human colon carcinoma); Caco-2 (human Caucasian colon adenocarcinoma); A431 (squamous cell carcinoma); MG-63 (osteosarcoma) and P815 (murine mastocytoma) [29][30][31][32][33][34][35][36][37]. This study has enriched the list of those cancer cell lines susceptible to 1,8-cineole and EO rich in1,8-cineole, and has demonstrated its potent effect on the ovarian cancer cell line (A2780).…”
Section: Discussionmentioning
confidence: 99%